SUSTAINING CANVA EDUCATION LEARNING ON ONLINE AND OFFLINE LEARNING: A CASE OF TEACHER'S BEST PRACTICE - Yulieda Hermaniar; Yasyir Fahmi Mubaraq (Proceeding International Conference on Digital Education and Social Science, 2022)
The shifting learning method as the pandemic stroke in early 2022 pushed all teachers in Indonesia to master technology in quite short time. The free online learning application such as google classroom, Edmodo, and Quizziz were used to conduct the teaching and learning process. The default setting on these applications were used to give instruction, attach assignment, or conduct assessment. In two years, the development of technological usage has improved significantly as many schools develop their own learning management system (LMS) as well as many teachers used various application to their online learning. One of the best practices used by the teacher in SMKN 4 Banjarmasin is integrating Canva Learning into the school’s learning management system. The teacher develops the various media using Canva Education in form of animated caption, animated video, full color scheduling, and online assessment. When the online learning ended as the pandemic is now under control, the teacher does adjustment on the Canva Education usage from online learning to face to face learning. Therefore, it is an interesting subject to study the adjustment of Canva Education usage from online to offline class in the teaching of English at SMKN 4 Banjarmasin. This research applied a qualitative study by using a case study method. The researchers conduct interview and observation to picture the teachers’ method and strategy in using Canva in her class.